Ontogenia de los estróbilos, desarrollo de los esporangios y esporogénesis de Equisetum giganteum (Equisetaceae) en los Andes de Colombia - Rincón Barón, Edgar Javier (2011)
Ontogeny of strobili, sporangia development and sporogenesis in Equisetum giganteum (Equisetaceae) from the Colombian Andes. Studies on the ontogeny of the strobilus, sporangium and reproductive biology of this group of ferns are scarce. Here we describe the ontogeny of the strobilus and sporangia, and the process of sporogenesis using specimens of E. giganteum from Colombia collected along the Rio Frio, Distrito de Sevilla, Piedecuesta, Santander, at 2 200m altitude. The strobili in different stages of development were fixed, dehydrated, embedded in paraffin, sectioned using a rotatory microtome and stained with the safranin O and fast green technique. Observations were made using differential interference contrast microscopy (DIC) or Nomarski microscopy, an optical microscopy illumination technique that enhances the contrast in unstained, transparent. Strobili arise and begin to develop in the apical meristems of the main axis and lateral branches, with no significant differences in the ontogeny of strobili of one or other axis. Successive processes of cell division and differentiation lead to the growth of the strobilus and the formation of sporangiophores. These are formed by the scutellum, the manubrium or pedicel-like, basal part of the sporangiophore, and initial cells of sporangium, which differentiate to form the sporangium wall, the sporocytes and the tapetum. There is not formation of a characteristic arquesporium, as sporocytes quickly undergo meiosis originating tetrads of spores. The tapetum retains its histological integrity, but subsequently the cell walls break down and form a plasmodium that invades the sporangial cavity, partially surrounding the tetrads, and then the spores. Towards the end of the sporogenesis the tapetum disintegrates leaving spores with elaters free within the sporangial cavity. Two layers finally form the sporangium wall: the sporangium wall itself, with thickened, lignified cell walls and an underlying pyknotic layer. The mature spores are chlorofilous, morphologically similar and have exospore, a thin perispore and two elaters. This study of the ontogeny of the spore-producing structures and spores is the first contribution of this type for a tropical species of the genus. Fluorescence microscopy indicates that elaters and the wall of the sporangium are autofluorescent, while other structures induced fluorescence emitted by the fluorescent dye safranin O. The results were also discussed in relation to what is known so far for other species of Equisetum, suggesting that ontogenetic processes and structure of characters sporoderm are relatively constant in Equisetum, which implies important diagnostic value in the taxonomy of the group.